2012
DOI: 10.1007/s10872-012-0146-4
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of glycerol dialkyl glycerol tetraethers, alkenones and polyunsaturated fatty acids in suspended particulate organic matter in the East China Sea

Abstract: We investigated the spatial distribution of glycerol dialkyl glycerol tetraethers (GDGTs), alkenones, and polyunsaturated fatty acids in particulate organic matter collected at four sites along a depth transect from the continental shelf to the Okinawa Trough in the East China GDGTs by an eastward current. At the slope and Okinawa Trough sites, TEX 86 -based temperatures were nearly constant in the water column deeper than 300 m and corresponded to temperatures at the surface and near-surface waters rather tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 49 publications
3
24
0
Order By: Relevance
“…In the northern OT, higher contents of unsaturated alkenones, observed in the upper water column of ∼ 20 m, and the estimated temperature are consistent with the modern observation based on the sediment trap samples (Nakanishi et al, 2012). Coccolithophore fluxes are high throughout the year, except for the summer season in the ECS (Tanaka, 2003).…”
Section: Salinitysupporting
confidence: 87%
“…In the northern OT, higher contents of unsaturated alkenones, observed in the upper water column of ∼ 20 m, and the estimated temperature are consistent with the modern observation based on the sediment trap samples (Nakanishi et al, 2012). Coccolithophore fluxes are high throughout the year, except for the summer season in the ECS (Tanaka, 2003).…”
Section: Salinitysupporting
confidence: 87%
“…Another study also suggested that alkenone-based temperatures represent thermocline temperatures because alkenone concentrations were high at the subsurface in the water column of the central Pacific Ocean (Lee and Schneider 2005). Nakanishi et al (2012b) investigated the vertical distribution of the alkenone concentration in the OT. They showed that the alkenone concentration is 100-200 ng/L at depths of 0-25 m, whereas it is almost 0 ng/L at depths below 100 m. Moreover, alkenone-based temperatures reconstructed from suspended particulate organic matter were consistent with in situ shallow (above 100 m) water temperatures (Nakanishi et al 2012b).…”
Section: Habitat Depth Of Alkenone Producersmentioning
confidence: 99%
“…Nakanishi et al (2012b) investigated the vertical distribution of the alkenone concentration in the OT. They showed that the alkenone concentration is 100-200 ng/L at depths of 0-25 m, whereas it is almost 0 ng/L at depths below 100 m. Moreover, alkenone-based temperatures reconstructed from suspended particulate organic matter were consistent with in situ shallow (above 100 m) water temperatures (Nakanishi et al 2012b). Thus, Nakanishi et al (2012b) suggested that alkenone-based temperatures derived from alkenones preserved in sediments can be used to reconstruct SSTs in the OT.…”
Section: Habitat Depth Of Alkenone Producersmentioning
confidence: 99%
See 1 more Smart Citation
“…As more becomes known about the habitat of Thaumarchaeota, the environmental conditions to which they respond, and the species most responsible for producing the GDGTs included in the TEX 86 index, it should become possible to refine the interpretation of TEX 86 derived temperature values. For example, recent work has demonstrated that GDGT production occurs primarily in subsurface waters of the ocean (Nakanishi et al, 2012;Basse et al, 2014). Subsurface growth of chemoautotrophic Thaumarchaeota is thought to result from the greater availability of NH 4 + generated from remineralization of particulate organic matter (POM) sinking out of the euphotic zone (Karner et al, 2001;Wuchter et al, 2006a;Schouten et al, 2013).…”
Section: Introductionmentioning
confidence: 99%